Herbert Robbins Selected Papers 1985
DOI: 10.1007/978-1-4612-5110-1_13
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of the Sequential Design of Experiments

Abstract: Introduction. Until recently, statistical theory has been restricted to the design and analysis of sampling experiments in which the size and composition of the samples are completely determined before the experimentation begins. The reasons for this are partly historical, dating back to the time when the statistician was consulted, if at all, only after the experiment was over, and partly intrinsic in the mathematical difficulty of working with anything but a fixed number of independent random variables. A ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
691
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 586 publications
(699 citation statements)
references
References 7 publications
4
691
0
4
Order By: Relevance
“…Tit-for-tat (TFT) has won both of the tournaments [16]. In 1987, when participants can memory more than one steps, Axelrod coded the game history and strategy in binary string and applied Genetic Algorithm to study Prisoner's Dilemma game [15]. The result is that some models in the strategy chromosome and TFT are in some ways similar.…”
Section: Background and Related Workmentioning
confidence: 96%
See 4 more Smart Citations
“…Tit-for-tat (TFT) has won both of the tournaments [16]. In 1987, when participants can memory more than one steps, Axelrod coded the game history and strategy in binary string and applied Genetic Algorithm to study Prisoner's Dilemma game [15]. The result is that some models in the strategy chromosome and TFT are in some ways similar.…”
Section: Background and Related Workmentioning
confidence: 96%
“…However, in 1992, the result of a lot of experiment researched by Nowak showed that cooperation can survive in the lattice network in Prisoner's Dilemma game [12]. Then, Axelrod gives an important contribution in 1980s [12,15,16]. Computer tournaments are conducted to find the strategy that plays best in a population playing Prisoner's Dilemma game [15].…”
Section: Background and Related Workmentioning
confidence: 98%
See 3 more Smart Citations